Pengaruh Viral Marketing Dan Online Costumer Review Terhadap Keputusan Pembelian E-Commerce Shopee Pada Generasi Z Kota Mataram - Auliya Rohmatunnisa; Indah Ariffianti; I Made Suardana (Kredibel: Jurnal Ilmiah Manajemen, 2025)
The study aims to test the effects of virmarketing and online custommer review on the purchase decisions of e-commerce shopee in the mataram city generation of z's, making the study variable 2 (two) an independent viral marketing (x1), online custommer review (x2) and the dependent variable of purchase decisions (y). The sample was taken using a nonsampling method with a kind of intergalactic sampling. Data gained by disseminating and filling out the Google form links to the 96 questionnaires on the z generation of mataram. Data analysis using linear regression. The study is determined that viral marketing with at count 5.425 > 1.985 t table, values 0,000<0.05, And an online costume review known value t count 6.678 > 1.985 t table, values 0,000<0.05. Indicating that viral marketing, custommer review online affected partial and simultaneous impact on purchase decisions. And dominant inan online costume review, its value is 0.497 greater than a viral marketing variable with a value of 0.404. The study has also been able to demonstrate that independent variables (viral marketing, online custommer review) can explain dependencies (purchasing decisions) by 60.7% while the rest by 39.3% are affected by other variables of the linear regression model.